Blind recognition of STBC-OFDM signals based on modified K-S test - Qing LING; Li-min ZHANG; Wen-jun YAN (Tongxin xuebao)
Aiming at the problem that existed blind classification of STBC-OFDM in multiple input single output (MISO) communication system,an efficient method for blind classification of space-time block coded orthogonal frequency-division multiplexing (STBC-OFDM) signals based on modified Kolmogorov-Smirnov (K-S) test was proposed,when a single receiver antenna was employed at the receiver.Firstly,the model of received STBC-OFDM signals in MISO systems was given.Secondly,with the correlation of the coding matrix of STBC-OFDM signals,and the discrimination features function provided by the empirical cumulative distribution (CDFs) of the received OFDM blocks was constructed.Finally,the distance between CDFs was tested by the two-sample K-S test,which could blindly classify the STBC-OFDM signals.The proposed algorithm didn't need the estimation of channel,noise statistics and modulation type,and consequently,was well suited for non-cooperative communication context.Theoretical analysis and experimental verify its validity.